Robust Hydrogenation of Nitrile and Nitro Groups to Primary Amines Using Ni2P as a Catalyst and Ammonia Borane under Ambient Conditions. Issue 11 (4th September 2017) - Zen, Yun‐Feng; Fu, Zi‐Cheng; Liang, Fei; Xu, Yong; Yang, Dan‐Dan; Yang, Zhi; Gan, Xin; Lin, Zhe‐Shuai; Chen, Yong; Fu, Wen‐Fu
Abstract: The selective hydrogenation of nitrile groups to primary amines is challenging owing to their high ability to produce secondary and tertiary amines. Herein, we report an efficient system for the hydrogenation of nitrile and nitro groups to primary amines catalyzed by Ni2 P nanoparticles in an aqueous H3 NBH3 solution under ambient conditions. The system exhibits high catalytic selectivity toward generating primary amines, resulting in good isolated yields. A combination of experiments and theoretical calculations shows that composite interactions among species on the catalyst surface alter the catalytic pathway. Abstract : A system has been developed for a highly efficient conversion of nitriles to primary amines using Ni2 P nanoparticles as a catalyst, and H3 NBH3 and H2 O as hydrogen sources, under ambient conditions. Substrates bearing nitro and cyano groups were hydrogenated simultaneously to give the desired products in high yields. This investigation shows that the combined interactions of reactant molecules on the catalyst surface alter the catalytic pathway.